2009
DOI: 10.1021/la8039913
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Organization of Cylindrical Sexithiophene Aggregates Measured by X-ray Scattering and Magnetic Alignment

Abstract: We have determined the internal organization of elongated sexithiophene aggregates in solution by combining small-angle X-ray scattering and magnetic birefringence experiments. The different aggregate axes can be probed independently by performing the experiments on magnetically aligned aggregates. We have found multiwalled cylindrical aggregates consisting of radially oriented sexithiophene molecules with pi-pi-stacking in the tangential direction, a structure that is considerably different from those previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…35) Recently, it has been reported that the aggregate morphology of sexithiophene materials can be tuned using different solvents from the results of X-ray scattering and magnetic orientation. 40) The solvent (o-DCB) for the formation of the P3BT nanowires in this study is different from that (p-xylene) for the formation of the P3HT nanowires in our previous study. 35) Therefore, the difference in magnetic orientation between the P3BT and P3HT nanowires is probably attributable to the difference in nanostructure between the nanowires, where the directions of -stacking are parallel to the long axes of the nanowires in the present P3BT nanowires (Fig.…”
Section: Effects Of Magnetic Processing On P3bt Nanowirescontrasting
confidence: 57%
“…35) Recently, it has been reported that the aggregate morphology of sexithiophene materials can be tuned using different solvents from the results of X-ray scattering and magnetic orientation. 40) The solvent (o-DCB) for the formation of the P3BT nanowires in this study is different from that (p-xylene) for the formation of the P3HT nanowires in our previous study. 35) Therefore, the difference in magnetic orientation between the P3BT and P3HT nanowires is probably attributable to the difference in nanostructure between the nanowires, where the directions of -stacking are parallel to the long axes of the nanowires in the present P3BT nanowires (Fig.…”
Section: Effects Of Magnetic Processing On P3bt Nanowirescontrasting
confidence: 57%
“…The entrance cone of the SAXS vacuum pipe as well as the WAXS detector are mounted on a moving support that can be displaced in order to fit equipment with large lateral size (up to 1-2 m). Several complex sample environments have successfully been implemented, such as superconducting magnets (McCulloch et al, 2011;Siemianowski et al, 2012;Gielen et al, 2009) or even fuel and waste gas handling systems for controlled soot formation experiments (Gardner et al, 2005).…”
Section: Beamline Descriptionmentioning
confidence: 99%
“…T6 can form different aggregates in protic polar solvents, with morphologies ranging from spherical structures [72], to needles [73], or rod-like helical assemblies and flat "crêpes" [74], where the morphology and resulting properties depend on the solvent and the fabrication method used. Small-Angle X-ray Scattering for the Study of Nanostructures and Nanostructured Materials [75].…”
Section: Magneto-saxsmentioning
confidence: 99%